An ER complex of ODR-4 and ODR-8/Ufm1 specific protease 2 promotes GPCR maturation by a Ufm1-independent mechanism. - Changchun Chen; Eisuke Itakura; Katherine P Weber; Ramanujan S Hegde; Mario de Bono (PLoS Genetics)
Despite the importance of G-protein coupled receptors (GPCRs) their biogenesis is poorly understood. Like vertebrates, C. elegans uses a large family of GPCRs as chemoreceptors. A subset of these receptors, such as ODR-10, requires the odr-4 and odr-8 genes to be appropriately localized to sensory cilia. The odr-4 gene encodes a conserved tail-anchored transmembrane protein; the molecular identity of odr-8 is unknown. Here, we show that odr-8 encodes the C. elegans ortholog of Ufm1-specific protease 2 (UfSP2). UfSPs are cysteine proteases identified biochemically by their ability to liberate the ubiquitin-like modifier Ufm1 from its pro-form and protein conjugates. ODR-8/UfSP2 and ODR-4 are expressed in the same set of twelve chemosensory neurons, and physically interact at the ER membrane. ODR-4 also binds ODR-10, suggesting that an ODR-4/ODR-8 complex promotes GPCR folding, maturation, or export from the ER. The physical interaction between human ODR4 and UfSP2 suggests that this complex's role in GPCR biogenesis may be evolutionarily conserved. Unexpectedly, mutant versions of ODR-8/UfSP2 lacking catalytic residues required for protease activity can rescue all odr-8 mutant phenotypes tested. Moreover, deleting C. elegans ufm-1 does not alter chemoreceptor traffic to cilia, either in wild type or in odr-8 mutants. Thus, UfSP2 proteins have protease- and Ufm1-independent functions in GPCR biogenesis.